2019
DOI: 10.3390/nano9040555
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Core-Shell Piezoelectric Nanofiber Yarns for Body Movement Energy Harvesting

Abstract: In an effort to fabricate a wearable piezoelectric energy harvester based on core-shell piezoelectric yarns with external electrodes, flexible piezoelectric nanofibers of BNT-ST (0.78Bi0.5Na0.5TiO3-0.22SrTiO3) and polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE) were initially electrospun. Subsequently, core-shell piezoelectric nanofiber yarns were prepared by twining the yarns around a conductive thread. To create the outer electrode layers, the core-shell piezoelectric nanofiber yarns were braided with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…In 2020, Mokhtari et al [143] fabricated a high-performance hybrid piezofiber composed of a PVDF and barium titanate (BT) nanoparticle (mass ratio 10:1). These fibers are knitted to fabricate a wearable energy generator with a power density of 87 µW cm -3 and a maximum voltage output of 4 V. In 2019, Sang et al [144] prepared a wearable piezoelectric energy harvester based on core-shell piezoelectric yarns prepared by twining the yarns around a conductive thread. The yarns were composed of flexible piezoelectric nanofibers of BNT-ST and PVDF-TrFE by electrospinning.…”
Section: Energy Harvesting Devicementioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Mokhtari et al [143] fabricated a high-performance hybrid piezofiber composed of a PVDF and barium titanate (BT) nanoparticle (mass ratio 10:1). These fibers are knitted to fabricate a wearable energy generator with a power density of 87 µW cm -3 and a maximum voltage output of 4 V. In 2019, Sang et al [144] prepared a wearable piezoelectric energy harvester based on core-shell piezoelectric yarns prepared by twining the yarns around a conductive thread. The yarns were composed of flexible piezoelectric nanofibers of BNT-ST and PVDF-TrFE by electrospinning.…”
Section: Energy Harvesting Devicementioning
confidence: 99%
“…This confirmed that it was possible to fabricate low-cost and lightweight electronic devices with reduced quantities of metal oxides and pressure sensing devices. between temperature and recovery time [94]; (e) Generated output voltages, output currents, output powers by Finger bending, knee and elbow movements [144]; (f) Pressure sensor embedded in the bottom of the insole or stuck on human arm and voltage generated by jumping, walking, running and different bending angles' elbows [123].…”
Section: Physical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy harvesting properties according to bending (b) elbow and (c) knee movements as the guard stitched in the elbow and knee parts, respectively. (d) Energy harvesting properties according to clapping movements as a cotton glove stitched in the effective area, and (e) energy harvesting properties according to walking and running movements as a shoe insole stitched in the effective area 28) .…”
Section: 지상현 윤지선mentioning
confidence: 99%
“…As a raw material, one‐dimensional nanofibers are widely used for designing and constructing products with two‐dimensional and three‐dimensional structures . These downstream products have unique optical, mechanical, electrical, magnetic and biological properties, which are widely used in the photocatalyst materials, biological textiles, electronic devices, gas‐sensitive materials and other fields. In recent years, the commonly used electrospinning templates are polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyethylene oxide (PEO), etc.…”
Section: Introductionmentioning
confidence: 99%